Public Library Play-based Early Literacy Programs: What is the Parental Experience? - Wilson-Scorgie, Dorothea Jane (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2022)
Many public libraries offer early literacy storytime programs to child patrons and their parents. Based on current research and best-practice periodicals, more children’s librarians are incorporating and modeling play-based activities in their storytime programs at the public library to emphasize the importance of parent-child interaction in guiding early literacy learning. Play as a method of learning is often underutilized and misunderstood by parents. This literature review aims to investigate the role of public libraries (and librarians) in informal early literacy education, the shift towards play-based practices in early literacy programs at the public library, the importance and significance of quality parent-child interaction in early literacy experiences, and the documentation of the experiences and perceptions of parents attending early literacy programs at the public library with their children. As previous studies correlate the benefits of parent-child interaction in play-based activities with early literacy learning, it is evident that further qualitative research into the actual experiences of parents attending play-based early literacy public library programs is needed in order to identify moreareas for improvement of public library services and storytime programs for child patrons and their parents.